Acute abducens nerve palsy following COVID-19 vaccination - Reyes-Capo, Daniela P.; Stevens, Shanlee M.; Cavuoto, Kara M. (Journal of AAPOS, 2021)
We report the case of a healthy 59-year-old woman who presented with an acute abducens nerve palsy 2 days after receiving the Pfizer-BioNTech COVID-19 vaccine. In adults, such palsies are typically caused by microvascular disease or compressive tumors, although they have also been described after routine vaccinations. Given the temporal relationship between vaccination and the onset of symptoms, the lack of preexisting medical conditions, and unremarkable magnetic resonance imaging, the patient's abducens nerve palsy was felt to be related to her vaccination. This case highlights the importance of recognizing the potential of a COVID-19 vaccine to have neurologic sequelae similar to those that as have been reported with the virus itself as well as with other vaccines.